Efektivitas Iklan Televisi dalam Menjangkau Khalayak Indonesia: Tinjauan Literatur Sistematis - M. Fathur Rohman (Universitas Muhammadiyah Palembang, 2025)
Purpose– This study intends to examine the efficacy of television advertising in reaching audiences in Indonesia by evaluating aspects such as message quality, appeal, frequency of delivery, and creative components. Design/methodology– The researcher used a systematic literature review to find articles, by using Google Scholar and Sage search sources. Three researchers independently selected articles based on inclusion and exclusion criteria, to collect relevant national and international literature. The search for articles was carried out using two search codes, “efektivitas iklan televisi” and “effectiveness of television advertising”. using the phrase “television advertising effectiveness”, three researchers This study successfully found 20 articles that functioned as research data, which were analyzed through data reduction, data presentation and drawing conlusions. Findings – This analysis demonstrates that the efficacy of television advertising in Indonesia is significantly influenced by visual appeal, broadcast frequency, and innovative content. Despite its enormous potential, micro-targeting and ad personalization are still rarely utilized. This study suggests evaluating advertising in a way that is more responsive to technology and behavior.